Curative anti-typhoid effect of Detarium microcarpum Guill. & Perr. (Leguminosae) hydroethanolic extract root bark based-on in vivo and molecular docking analyses. (10th May 2023) - Mbock, Michel Arnaud; Kamkumo, Raceline Gounoue; Shukla, Rohit; Fouatio, William Feudjou; Fokou, Patrick Valère Tsouh; Tsofack, Florence Ngueguim; Noussi, Clarice Djouwoug; Fifen, Rodrigue; Nkengfack, Augustin Ephrem; Singh, Tiratha Raj; Ndjakou, Bruno Lenta; Sewald, Norbert; et al.
Abstract: Ethnopharmacological relevance: Detarium microcarpum is used to treat typhoid fever, a major public health problem, by indigenous population in Africa. Though its preventive activities have been documented, the curative effect is still to be confirmed. Aim of the study: This study aimed at evaluating the curative effects of the hydroethanolic extract of Detarium microcarpum root bark on Salmonella typhimurium -induced typhoid in rat and exploring the in-silico inhibition of some bacterial key enzymes. Study design: In vitro antioxydant, in vivo antisalmonella of the extract and in silico molecular docking assay on the isolated compounds were carried out to explore the anti-salmonella effects of Detarium microcarpum . Material and methods: The in vitro antioxidant properties of the extract were evaluated using DPPH, ABTS and FRAP tests. The anti-salmonella activity of the extract was assessed through feacal sample from Salmonella typhimurium -infected rat cultured in Salmonella-Shigella agar (SS agar) medium. The affinity of isolated compounds (Rhinocerotinoic acid and Microcarposide) from the extract were performed on four key enzymes (Adenylosuccinate lyase, Acetyl coenzyme A synthetase, Thymidine phosphorylase and LuxS-Quorum sensor) using molecular docking simulation to elucidate the molecular level inhibition mechanism. Results: Crude extract of D. microcarpum root bark showed variable activities on DPPH (RSa50: 6.09 ± 1.04 μg/mL), ABTS (RSa50: 24.46 ± 0.27), and FRAP (RSa50: 23.30 ± 0.23). The extract at all the doses exhibited significant healing effect of infected rats, with the complete clearance. The extract restored hematological, biochemical and histological parameters closed to the normal control. The molecular docking results indicates that rhinocerotinoic acid and microcarposide present more affinity to the LuxS-Quorum sensor and Acetyl coenzyme A synthetase protein as compared to the others. Conclusion: These results demonstrate potent anti-typhoid activities of the hydroethanolic of Detarium microcarpum root bark extract through antioxidant properties and high inhibitory affinity of its compounds on some bacterial key enzymes that justify its use as traditional medicine to typhoid fever. Graphical abstract: Image 1 Highlights: Salmonellosis-infected rats respond favorably to the hydroethanolic extract of Detarium microcarpum. The study found that Detarium microcarpum displayed antioxidant properties. Detarium microcarpum active principles inhibit the LuxS-quorum sensor protein and Acetyl Coenzyme A synthetase.